PENGARUH SELF EFIKASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU DI MODERASI KEPEMIMPINAN TRANSFORMASIONAL (Studi pada Guru Tetap SMP Negeri sub rayon 05 Kayen, Kabupaten Pati) - Maskup, 12.5202.0145; Sutomo, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimed to examine the effect of self-efficacy and organizational commitment on teacher performance in moderation transformational leadership studies based on teacher fixed SMP sub-rayon 05 Kayen, Pati. The usefulness of this study to clarify and extend previous research on the influence of self-efficacy and organizational commitment on teacher performance remains SMP sub-rayon 05 Kayen, Pati with transformational leadership as a moderating variable. This research uses a quantitative approach that is supported by descriptive and qualitative analysis. The sample was the whole teachers remain SMP sub-rayon 05 Kayen, Pati totaling 151 people. Research using proportional random sampling technique to sample size using the formula of Slovin, by determining the proportion of the population that is used as a sample study. Techniques of data analysis starts from the test instrument, the classical assumption test, test models, test of goodness of fit, and hypothesis. The study of permanent teachers SMP sub-rayon 05 Kayen, Pati showed that: (1) self-efficacy significantly influence the performance of teachers, (2) organizational commitment does not significantly affect the performance of teachers, (3) significant influence of transformational leadership on teacher performance, (4) ineffective transformational leadership moderates the influence of self-efficacy on teacher performance, and (5) effective transformational leadership moderates the influence of organizational commitment on teacher performance. Keywords: self-efficacy, organizational commitment, teacher performance, and transformational leadership.